The Effect of Amoxicillin-Clavulanate and Actifed Versus Actived Only in treatment of Otitis Media with Effusion - Muhei Rasheed, Ahmed; Hayder Taha, Yusra (Journal of the Faculty of Medicine Baghdad, 2008)
Background: Otitis media with effusion(OME)is a common cause of deafness in children with subsequent impairment of speech development and scholastic difficulties.Treatment remains controversial. Aim: To study the effect of amoxicillin-clavulanate in treatment of OME Patients and methods: A prospective study of a target sample consisting of sixty children under the age of 12 years presented with chief complaints duration for at least 6 weeks and on examination there were bilateral red and retracted tympanic membranes without oversized adenoids and no underlying causes require surgical correction e.g cleft palate.The patients were divided into two groups;group A which received Actifed for 4 weeks and group B which received Actifed +Amoxicillin-clavulanate for 4 weeks treatment course.After complete history and otolaryngological examination,all the patients were sent to x-ray of postnasal space( to exclude oversized adenoids),audiometry and tympanometry.Assessment was repeated at the end of 2 and 4 weeks of treatment course including audiometry and tympanometry.The response to treatment in group B was compared to that in group A at the end of 4 weeks treatment course.In this study,we refered to improvement in otoscopic findings and tympanometry results to show the response to 4 weeks treatment course. Results: Eight patients(25.81%)in group A have shown response to treatment at the end of 4 weeks treatment course,while the response in group B was seen in 15 patients( 51.72%). Conclusion: Amoxicillin-clavulanate has statistically significant effect in treatment of otitis media with effusion(OME)in short term follow-up and the clearance of middle ear efussion in response to amoxicillin-clavulanate indicates that bacterial infection may play a role in the aetiology of OME.